1986
DOI: 10.1515/cclm.1986.24.1.11
|View full text |Cite
|
Sign up to set email alerts
|

Catalytic Enzyme Activity Concentration in Plasma of Man, Sheep, Dog, Cat, Rabbit, Guinea Pig, Rat and Mouse. Approach to a Quantitative Diagnostic Enzymology. I. Communication

Abstract: Summary:For the most convenient laboratory animals in experimental medicine such äs the sheep, dog, cat, rabbit, guinea pig, rat and mouse, the catalytic concentrations of seventeen enzymes and the protein and albumin concentrations in plasma were determined. The corresponding data for man were taken from the literature. The experimental conditions were selected so äs to minimize the influence on catalytic activity, variance and statistical distribution pattern of such factors äs handling procedures, the choic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
11
1

Year Published

1991
1991
2015
2015

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 37 publications
2
11
1
Order By: Relevance
“…It would be of considerable practical value to continue feeding the rabbits with the same levels of dehydrated olive cake pulp in fodder mixes (for several months or even years) and to monitor the influence of that feed component on serum AP activity. The values of AP activity found in this study fully correspond to those quoted as physiological for rabbits by Grötsch and Hajdu (1979), Lindena and Trautschold (1986), and Hewit et al (1989). However, the values found by us are higher than those reported by Dabew et al (1976) and Yu et al (1979), and lower than those published by Liker et al (1998).…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…It would be of considerable practical value to continue feeding the rabbits with the same levels of dehydrated olive cake pulp in fodder mixes (for several months or even years) and to monitor the influence of that feed component on serum AP activity. The values of AP activity found in this study fully correspond to those quoted as physiological for rabbits by Grötsch and Hajdu (1979), Lindena and Trautschold (1986), and Hewit et al (1989). However, the values found by us are higher than those reported by Dabew et al (1976) and Yu et al (1979), and lower than those published by Liker et al (1998).…”
Section: Discussionsupporting
confidence: 91%
“…It can therefore be concluded that consumption of feed containing different levels of dehydrated olive cake pulp caused no significant changes in serum GGT activity of rabbits after the 56-day period of experimental fattening. The GGT activities found in all groups of rabbits correspond to the values reported by Liker et al (1998), and are higher than those described by Yu et al (1979), Lindena and Trautschold (1986), and Lepitzki and Woolf (1991).…”
Section: Discussionsupporting
confidence: 75%
See 1 more Smart Citation
“…The CK activity in rabbits is considerably higher than in humans. Increased levels of CK, but also of LD and AST could be a consequence of the blood taking procedure, due to damaged muscle (Mitruka and Rawnstey 1981;Lindena and Trautschold 1986).…”
Section: Discussionmentioning
confidence: 99%
“…As with any experiment, values can vary significantly between breeds, laboratories, methods of sampling and measurement, and individual rabbits due to age, sex, breed, health, handling, and husbandry (Hewitt et al, 1989;Lidena and Trautschold, 1986;Mitruka and Rawnsley, 1981;Wolford et al, 1986;Yu et al, 1979). It is important to recognize, however, that most of these values have been obtained through the study of adult New Zealand White rabbits.…”
Section: B Normative Physiological Valuesmentioning
confidence: 99%